Experimental investigation on the performance degradation of grouting materials in karst erosion environment - Tang, Wang; Xie, Mengshan; Fang, Xinghua; Huang, Chengxi; Mo, Cuiliu; Chen, Yongjun (Frontiers in Earth Science, 2025)
The fundamental cause of leakage in grouting curtains of dams in karst areas lies in the localized damage induced by performance degradation of the curtain under seepage-induced erosion. This work investigated the degradation mechanisms of grouting curtains exposed to karst water erosion by analyzing the mechanical and microstructural evolution of cement-grouted stone (CGS) and cement-clay-grouted stone (CCGS). The results indicate that both materials experience progressive deterioration in mechanical properties, with CCGS demonstrating significantly higher vulnerability. After 120 days, the compressive strength of CGS decreased from 32.89 MPa to 20.03 MPa, while the strength of CCGS declined sharply from 3.89 MPa to 2.03 MPa. Porosity increased from 26.06% to 33.91% for CGS and from 58.04% to 77.01% for CCGS. Microstructural analysis revealed that karst water induced chemical erosion and structural damage in both materials, with CCGS exhibiting accelerated degradation due to weaker cementitious bonding and higher initial porosity, which facilitated ion penetration and reaction-induced damage. The findings highlight the inferior durability of cement-clay composites under karst water conditions and provide critical insights for optimizing grouting materials in karst-prone environments.